Generation of an in vitro model of β‐thalassemia using the CRISPR/Cas9 genome editing system. Issue 2 (9th October 2019) - Ajami, Monireh; Atashi, Amir; Kaviani, Saeid; Kiani, Jafar; Soleimani, Masoud
Abstract: β‐Thalassemia is a common monogenic disease characterized by defective β‐globin chains synthesis. In vitro β‐thalassemia‐related research on increasing β‐like globin genes or identification of factors reducing the severity of the disease, has been performed on mouse erythroleukaemia or K562 cell lines. The aim of this study was the production of an in vitro model of β‐thalassemia using the highly efficient CRISPR‐Cas9 system. Embryonic stem (ES) cells were nucleofected with guide RNA (gRNA)‐Cas9 expression vectors. Molecular testing was done on extracted DNA to assess Hbb‐b1 mutation. Analysis of transcription factors and hemoglobin genes were evaluated using quantitative reverse transcription‐polymerase chain reaction following erythroid differentiation of ES cells. Sequencing data confirmed Hbb‐b1 knockout alleles. Significant expression of erythroid transcription factors was observed in wild‐type, Hbb‐b1 +/− and Hbb‐b1 −/− groups ( P < .001). Compared with the wild‐type group, the absolute number of Hbb‐b1 mRNA in Hbb‐b1 +/− group significantly decreased from 6.44 × 10 6 to 3.23 × 10 6 copy number ( P < .01), whereas in Hbb‐b1 −/− group had zero expression. The CRISPR/Cas9‐mediated Hbb‐b1 knockout in ES cells provides accessibility to an in vitro thalassemia model following erythroid differentiation. Considering the need for in vitro and mouse models to investigate the molecular basis of β‐thalassemia which also enables testing of therapeutic approaches, this method can be utilized to produce a mouse model of β‐thalassemia intermedia (Hbbth1/th1). Abstract : Use of dual single guide RNA (sgRNA) CRISPR/Cas9‐mediated Hbb‐b1 knockout, as an in vitro thalassemia model ( Hbb‐b1 −/− group). Greater expression of Hbb‐b2 was seen in erythroid differentiation of Hbb‐b1 −/− and Hbb‐b1 +/− ES cells. Same potential of erythroid differentiation in ES cells with wild‐type and modified Hbb‐b1 .